The "Safe Sex" Conundrum: Anticipated Stigma From Sexual Partners as a Barrier to PrEP Use Among Substance Using MSM Engaging in Transactional Sex. - Biello, Katie B; Oldenburg, Catherine E; Mitty, Jennifer A; Closson, Elizabeth F; Mayer, Kenneth H; Safren, Steven A; Mimiaga, Matthew J (AIDS and behavior, 2016)
Pre-exposure prophylaxis (PrEP) is efficacious for HIV prevention when taken consistently; however, barriers to PrEP use are poorly understood among individuals who could benefit from PrEP, including men who have sex with men (MSM) who engage in transactional sex (i.e., sex exchanged for money or drugs). Two hundred and thirty-seven HIV-uninfected, PrEP-naive MSM reporting concurrent substance dependence and sexual risk completed a questionnaire on PrEP use barriers. Barriers to PrEP use for MSM who engaged in recent transactional sex (22 %) versus those who had not were compared using an ecological framework. Individual (e.g., HIV stigma, substance use) and structural (e.g., economic, healthcare) barriers did not differ (p > 0.05). MSM who recently engaged in transactional sex were more likely to report that anticipated stigma from primary and casual partners would be barriers to PrEP use. Assessing recent transactional sex may help identify men who may need additional counseling to avoid anticipated stigma so they can integrate PrEP into their lives.